Isolasi dan Uji Aktivitas Antioksidan Senyawa Flavonoid dari Batang Bauhinia Exwlsa. - Tanjung, Mulyadi (Penerbitan Unpad Press, Universitas Padjajaran, Indonesia, 2014)
ABSTRACT Two flavonoids, 6C,7-O-dimethyl aromadendrin (1) have and ploretin (2) been isolated from the bark of Bauhinia excelsa. The structure of 6C,7- O-dimethyl aromadendrin (1) have and ploretin (2) been elucidated based on its spectroscopic data, including UV, MS 1D and 2D NMR spectra. The activity of radical scavenging against 2,2-diphenyl-1-picrylhydrazyl (DPPH), showing their IC50 were 1512.1 μM. The results indicate that as 6C,7-O-dimethyl aromadendrin and phloretin were inactive